A deoxyadenylate kinase activity associated with polynucleotide phosphorylase from Micrococcus luteus - Craine, Jonathan E. (1976)
We report here the presence of two enzymatic activities associated with highly purified preparations of polynucleotide phosphorylase from Micrococcus luteus. The first, a nuclease activity, which is not separated from the phosphorylase on hydroxylapatite, may be due to substitution of H(2)O for phosphate in the phosphorolysis reaction. The second ac tivity, a deoxyadenylate kinase, the bulk of which is not resolved from the phosphorylase using gel filtration, sucrose density gradient centrifugation, DEAE-Sephadex, or hydroxylapatite chromatography, may represent a new activity of polynucleotide phosphorylase or be due to an enzyme which is tightly bound to the phosphorylase. Several properties of the kinase are described and its possible significance with respect to the overall enzyme mechanism is discussed.